2016
DOI: 10.4067/s0034-98872016000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de la acupuntura en el tratamiento del dolor agudo postquirúrgico en adultos, en comparación con tratamientos activos o con acupuntura simulada

Abstract: Artículos de InvestIgAcIón (Rev Med Chile 2016; 144: 325-332)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…3 Lao and colleagues 4 observed that the pain-free duration in patients with third molar extractions under acupuncture analgesia was significantly longer than that in the same surgery patients experiencing placebo acupuncture; and the pain intensity after oral surgery was significantly lower in the former surgery patients. Moreover, Fuentealba and Biagini 5 reported that in the postoperative period of tonsillectomy, acupuncture interventions reduced pain by 36% and 22% at 20 min and 2 h, respectively. In patients undergoing knee replacement, acupuncture intervention reduced pain by 2% and analgesic consumption by 42%.…”
Section: Introductionmentioning
confidence: 99%
“…3 Lao and colleagues 4 observed that the pain-free duration in patients with third molar extractions under acupuncture analgesia was significantly longer than that in the same surgery patients experiencing placebo acupuncture; and the pain intensity after oral surgery was significantly lower in the former surgery patients. Moreover, Fuentealba and Biagini 5 reported that in the postoperative period of tonsillectomy, acupuncture interventions reduced pain by 36% and 22% at 20 min and 2 h, respectively. In patients undergoing knee replacement, acupuncture intervention reduced pain by 2% and analgesic consumption by 42%.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that percutaneous peripheral nerve stimulation can be used to treat acute postoperative pain of various types of surgeries [ 32 ]. Acupuncture intervention and transcutaneous electrical nerve stimulation (TENS), being similar to percutaneous peripheral nerve stimulation, have been proved to be effective for relieving postoperative pain of neck surgery [ 9 , 10 , 33 ], tonsillectomy [ 7 , 11 , 34 ], back surgery [ 5 ], dental procedures [ 7 , 35 ], and knee replacement [ 7 ]. Our previous clinical study [ 33 ] also showed that EA of LI18 and LI4-PC6 had a good effect in inducing analgesia and controlling the mean arterial pressure (MAP) and heart rate (HR), and reduced the anesthetic dose required by patients undergoing thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Low numbers of studies of heterogenous design and quality limit the reliability of data, however, and more studies are needed to reach aconsensus. [60][61][62][63] Evidence for cold therapy exists so far only in randomized controlled trials for a variety of surgical procedures, including hernia repair, A-V fistula creation, and dental surgery. 59,[64][65][66][67][68][69][70][71][72] Other methods also need further study even though they are endorsed by various institutions.…”
Section: Recommendations and Summary Of Evidencementioning
confidence: 99%